Pendampingan Strategi Digitalisasi Pemasaran dan Pencatatan Keuangan BUMDes dalam Mendukung Pengembangan Pariwisata Berkelanjutan di Kawasan Danau Toba Samosir - Rena Nainggolan; Marlyna I. Hutapea; Eviyanti Novita Purba; Eva Julia Gunawati Harianja; Jamaluddin Jamaluddin; Gortap Lumbantoruan; Darwis R. Manalu; Resianta Perangin-angin; Rimbun Siringoringo; Roni J. Simamora; Rijois I. E Saragih (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
Village Owned Enterprises (BUMDes) are strategic economic institutions. To support village economic independence, BUMDes operate in villages. However, most BUMDes still face big challenges in product marketing and financial record management, which are still done manually and use outdated methods. The purpose of this article is to explore how digital marketing systems and digital financial recording contribute to improving the performance and competitiveness of BUMDes. This study uses recent literature research (2020–2025) to analyze digital marketing strategies based on social media, websites, and e-commerce, as well as the implementation of digital-based Accounting Information Systems (AIS) for BUMDes financial recording. The research results show that using digital technology increases sales volume, market reach, transparency, and accountability in managing BUMDes finances.Keywords: soft skills, tech leadership, vocational high school, industry readiness, community service. Samosir Regency, which is one of Indonesia's five Super Priority Destinations designated by the government and is part of the Lake Toba National Tourism Strategic Area (KSPN), has a growing need for digitalization. Village-owned enterprises (BUMDes) in Samosir have a great opportunity to drive the village tourism economy, but they can only succeed if supported by a digital marketing system that can promote local products and tourism potential to tourists. BUMDes in Samosir have a huge opportunity to become the driving force of the village tourism economy, but they can only succeed if backed by a digital marketing system that can promote local goods and tourism potential to both domestic and foreign tourists, as well as a clear and accountable financial recording system. Limitations in human resources, technology infrastructure, and internet access in rural areas are major challenges. To realize smart BUMDes To create smart and competitive Village-Owned Enterprises (BUMDes), especially to support sustainable tourism development in the Lake Toba–Samosir area, continuous mentoring, digital literacy training, and support from local government policies are needed